Utilización de blogs y redes sociales en el ejercicio periodístico independiente en la provincia de El Oro. - Morales Guajala, Estefanía del Pilar (2016)
The need to communicate to other people is innate, since man was born; But thanks to the fact that from the beginning we communicate through gestures and signs, this has been creating new forms of communication, since a short time after the internet was implemented and these new possibilities are part of the development of numerous applications on the Internet that facilitate the Communication between people; As manifested by Ailexandre & Ferrer; Who from their point of view the internet provides a quick and accurate information to the people. Social networks and blogs are now part of new ways of communicating to others; The analysis of the publication scenarios performed by independent journalists in the province of El Oro has been able to generate conclusions about the use and management of these networks; As well as the interaction they provide to their audiences. The forms of research that were carried out in this titration work were from a mixed quantitative and qualitative approach.